HSFAS mediates fibroblast proliferation, migration, trans-differentiation and apoptosis in hypertrophic scars via interacting with ADAMTS8 - Ma Fang; Liu Honglin; Xia Tongtong; Zhang Zhenghao; Ma Shengchao; Hao Yinju; Shen Jiangyong; Jiang Yideng; Li Nan (Acta Biochimica et Biophysica Sinica, 2023)
Hypertrophic scar (HS) is one of the most common sequelae of patients, especially after burns and trauma. The roles of regulatory long noncoding RNAs (lncRNAs) in mediating HS remain underexplored. Human hypertrophic scar-derived fibroblasts (HSFBs) have been shown to exert more potent promoting effects on extracellular matrix (ECM) accumulation than normal skin-derived fibroblasts (NSFBs) and are associated with enhanced HS formation. The purpose of this study is to search for lncRNAs enriched in HSFBs and investigate their roles and mechanisms. LncRNA MSTRG.59347.16 is one of the most highly expressed lncRNAs in HS detected by lncRNA-seq and qRT-PCR and named as hypertrophic scar fibroblast-associated lncRNA (HSFAS). HSFAS overexpression significantly induces fibroblast proliferation, migration, and myofibroblast trans-differentiation and inhibits apoptosis in HSFBs, while knockdown of HSFAS results in augmented apoptosis and attenuated proliferation, migration, and myofibroblast trans-differentiation of HSFBs. Mechanistically, HSFAS suppresses the expression of A disintegrin and metalloproteinase with thrombospondin motifs 8 (ADAMTS8). ADAMTS8 knockdown rescues downregulated HSFAS-mediated fibroblast proliferation, migration, myofibroblast trans-differentiation and apoptosis. Thus, our findings uncover a previously unknown lncRNA-dependent regulatory pathway for fibroblast function. Targeted intervention in the HSFAS-ADAMTS8 pathway is a potential therapy for HS.